Indian marine fishery resources: optimistic present, challenging future - Sathianandan, T V; Jayasankar, J; Kuriakose, Somy; Mini, K G; Mathew, Wilson T (Indian Journal of Fisheries, 2012)
Marine fish production from capture fisheries in India has increased by about six fold during the past six decades. Exportearnings from the marine sector crossed 12,000 crores in 2010-11 and gross revenue through marine fish landings at the pointof first sales was about 20,000 crores. Marine products are now exported from India to nearly 100 countries. Monitoring theharvest of different marine fishery resources is very much essential for planning and implementing policies for sustainedproduction from the sea. The dynamic changes in the landings of marine fishery resources over the last six decades wereexamined after classifying them into 26 different resource groups. Decadal averages of landings of different resource groupswere compared using Student’s t test and coefficient of variation was worked out for each decade. Present status of eachresource group was examined separately based on a simple criterion. Out of the 26 groups examined, 18 were found to beunder the ‘abundant class, 5 under ‘less abundant’ class and one each under ‘declining’, ‘depleted’ and ‘collapsed’ classes.Elasmobranchs, threadfins, ribbonfishes, mullets and flatfishes are the five resource groups falling under ‘less abundant’class. White fish falls under ‘declining’ class, flying fishes under ‘depleted’ class and unicorn cod under ‘collapsed’ class.All the other groups fall under the ‘abundant’ class indicating that most of the resources (73%) are in healthy condition. The‘depleted’ and ‘collapsed’ classes require management interventions for the recovery of the resources and the group fallingunder ‘declining’ class needs caution and care to prevent further reduction in the stock.